The Effect of Promotion, Service Quality, Online Customer Rating on Purchase Decisions For Gojek Services in Medan City - Pasaribu, Lidya Natalia; Gracia, Jennifer; Sinaga, Dina Maylentina Br; Saputri, Khana (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the influence of promotions, service quality, and online customer ratings on purchasing decisions for Gojek services in Medan City. The method used is quantitative research with a purposive sampling technique, involving 100 respondents who are active Gojek users aged 18-30 years. Data were analyzed using path analysis with the help of SmartPLS software version 4. The results of the study indicate that partially, promotions have no significant effect on purchasing decisions, while service quality and online customer ratings have a positive and significant effect. Simultaneously, these three variables have a significant positive effect on purchasing decisions with a contribution of 87.6%. These findings indicate that service quality and online customer ratings are the main factors in purchasing decisions for Gojek services by Medan residents. This study provides recommendations for increasing the effectiveness of promotions and strengthening service quality and managing online customer ratings to increase customer loyalty.